The effect of information technology devices on student learning outcomes: a systematic literature review - Edy Sasmito; Garianto; Sutrisni Andayani (Lentera Negeri, 2026)
Objective of this study is to systematically synthesize empirical evidence on the effect of Information Technology (IT) devices on student learning outcomes and to identify multi-level factors that moderate this relationship, guided by the Technological Pedagogical Content Knowledge (TPACK) framework, Cognitive Load Theory (CLT), and Self-Determination Theory (SDT). Method employed is a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. Literature searches were conducted in Google Scholar, Scopus, and ERIC databases using Boolean search strings: ("information technology" OR "ICT" OR "digital learning" OR "educational technology") AND ("learning outcomes" OR "academic achievement" OR "student performance") AND ("education" OR "school" OR "higher education") within the 2019–2025 range. After identification, screening, and quality assessment using the JBI Critical Appraisal Checklist and Cochrane Handbook criteria (minimum score ≥70%), 56 articles met the inclusion criteria. Inter-rater reliability for screening was assessed using Cohen's kappa (κ = 0.84, 95% CI [0.78, 0.90]), indicating strong agreement. Due to high heterogeneity (I² > 75%), narrative synthesis was employed rather than statistical meta-analysis. Results show that 80.4% of studies reported significant positive effects with effect sizes (Cohen's d) ranging from moderate to very large (d = 0.85 to d = 2.58). Influencing factors include teacher competence (TPACK) appearing in 73.2% of studies, student readiness (attitudes and intrinsic motivation) in 66.1%, school infrastructure in 57.1%, and contextual factors such as education level (highest effect in senior high school) and subject area (science > mathematics) in 53.6%. Conclusion of this study is that information technology acts as an effective catalyst for improving learning outcomes, but its effectiveness depends on the synergy between teacher pedagogical competence, student readiness, institutional support, and contextual suitability. Recommended policy implications include the need for continuous TPACK training for teachers and addressing the digital divide in schools.